(untitled) (Research, Society and Development, 2024)
Introduction: Zika virus (ZIKV) infection is a serious public health issue, linked to rapid spread and microcephaly, causing severe neurological damage, especially if contracted during pregnancy. Transmitted by Aedes aegypti and Aedes albopictus mosquitoes, Zika increases the risk of congenital complications such as cerebral palsy and epilepsy. Genetic factors may influence the severity of the infection. Despite gaps in knowledge, the link between ZIKV and microcephaly is clear, emphasizing the need for early diagnosis and rigorous monitoring. Methodology: This study analyzed suspected cases of Zika Congenital Syndrome (ZCS) in Brazil from 2017 to 2022, using data from RESP-Microcephaly. A quantitative approach was used to compare characteristics such as congenital alterations, gestational age, sex, birth weight, and regional prevalence. The data, derived from DataSUS Tabnet, are anonymous and public. The study provides insights into the distribution and temporal characteristics of ZCS in the country, with five figures illustrating the analyses. Results: A total of 8,490 suspected cases of ZCS were analyzed. There was a continuous decrease in notifications over the years, with 2017 registering the highest number. Microcephaly was the most common congenital alteration (74.07%). Notifications predominated in the third trimester, with a higher incidence in males. The Southeast and Northeast regions had more cases, proportionally to the population. Notifications decreased over the period, with occasional increases in some regions and years. Discussion: The Zika virus caused an increase in microcephaly in Brazil. The country launched RESP-Microcephaly to monitor ZCS. There has been a reduction in cases since 2017, linked to policies combating Aedes mosquitoes. The majority of cases occur in the third trimester, predominantly in boys. The research provides insights for future interventions in maternal and child health. Conclusion: The Zika virus epidemic is concerning, especially in regions with limited resources. ZCS, caused by Zika, leads to serious consequences such as microcephaly and other congenital anomalies, with a difficult diagnosis and no specific treatment. Future studies are needed for prevention and diagnosis, including preventing vertical transmission and identifying biomarkers for early interventions.